Improving work Discipline and Employee Performance in “Kud Tani Makmur” - Nurjanah, Dita Tri; Nuvriasari, Audita (Asian Journal of Community Services, 2023)
Village Unit Cooperatives or in Indonesian called “Koperasi Unit Desa” (KUD) have an important role in improving the welfare of the community, especially farmers. This community service aims to improve work discipline and employee performance at KUD Tani Makmur, a KUD that operates in the agricultural and savings and loan sectors. This community service is carried out using methods through the transfer of knowledge and technology through outreach activities on the use of performance appraisal forms to measure performance and increasing awareness of employee discipline through the creation of x banners containing employee code of conduct. The work program implemented can be a solution to improve work discipline and employee performance in cooperatives.